Studi Kasus Tentang Perilaku Membolos Siswa Di Smp N 3 Bukittinggi - Annisa Novia; Yeni Afrida; Nelvy Yanti (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
This research was motivated by the frequent cases of repeated truancy in SMP Negeri 3 Bukittinggi which became the driving force of this research. sTherefore, research on truant behavior in students needs to be done to determine the types of truant behavior, factors that encourage students to do truant behavior, how parents can influence truant behavior, the impact of truant behavior, and how students' perceptions of truant behavior and how Guidance And Counseling teachers handle it. Participants in this study were grade VIII teenagers who often skipped school. Data collection methods include interviews, documentation, and observation. The findings of this study show that there are two types of truant behavior carried out by students at SMP Negeri 3 Bukittinggi, namely truant entirely and only during designated class hours. Factors that encourage students to behave truant include factors from themselves, family factors and environmental factors. Parental participation in truant behavior largely refers to the fact that based on parenting, parents are not directly involved in their child's truant behavior. The impact of truant behavior can be psychological, academic, or non-academic. Guidance and counseling teachers respond to this impact by providing information services, contacting parents, working with principals and homeroom teachers, and calling students who exhibit truant behavior for guidance on both the student and parent side